(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to measure the impact of technology on improving the quality of school canteen services, applied to elementary schools in the Asir region. To achieve this, the study adopted a descriptive-analytical approach. Data were collected using an electronic questionnaire distributed to a purposive stratified sample of (150) parents of elementary school students in the Asir region during the second semester of the academic year 1447 AH. The study tool consisted of three main dimensions: operational and financial efficiency, health and food quality, and transparency and parents’ satisfaction. The results showed that the impact of technology on improving canteen service quality was high, with an overall arithmetic mean of (3.98). Hypothesis testing confirmed a statistically significant positive correlation between technology use and service quality dimensions. Furthermore, results revealed statistically significant differences attributed to the school location variable in favor of Abha city schools, while no significant differences were found attributed to gender or educational qualification. The study recommended generalizing the smart canteen model, improving technical infrastructure in rural areas, and mandating electronic payment systems for canteens to enhance transparency and efficiency in alignment with Saudi Vision 2030.